The “Well-Dressed Snake Personality”: An Insight into Narcissistic/Psychopathic Personalities - Orsolini, Laura; Cicolini, Angelica; Salvi, Virginio; Volpe, Umberto (Journal of Psychology and Psychotherapy Research, 2022)
How many kinds of malevolent characters are out there? In line with Paulhus and Williams (2002) the answer is three, namely the Dark Triad of Machiavellianism, Narcissism, and Psychopathy. Dark traits (DT) are associated with emotional deficits, exploitation, immoral strategic thinking, and risky behaviors. All three traits have been largely investigated mainly during the last decades. The purpose of this paper is to provide an overview about the available literature regarding the characteristics of personality traits associated with the DT, by focusing on the main consequences of the DT from a psychopathological and psychiatric perspective. Studies found a strong association between DT traits and several types of negative psychosocial outcomes such as substance use, sexual promiscuity, aggression, and crime. Nevertheless, there is specific literature showing the advantages of scoring high DT traits, for example the assumption of positions of authority over other people, and the expression of low levels of social anxiety. Although the literature mainly focuses on the consequences that DT traits may have for society in general, there is a lack of studies investigating the personal repercussions, in the psychopathological and/or psychiatric dimensions in those individuals scoring high DT traits. Therefore, further research is needed to clarify how the different personality dark traits may interact with each other and modulate not only the individual’s life choices but also how and whether DT traits may predispose or not to the onset of a specific psychiatric disorder.